2011
DOI: 10.1105/tpc.111.085266
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor–Dependent Chromatin Remodeling at Heat Shock and Copper-Responsive Promoters in Chlamydomonas reinhardtii    

Abstract: How transcription factors affect chromatin structure to regulate gene expression in response to changes in environmental conditions is poorly understood in the green lineage. To shed light on this issue, we used chromatin immunoprecipitation and formaldehyde-assisted isolation of regulatory elements to investigate the chromatin structure at target genes of HSF1 and CRR1, key transcriptional regulators of the heat shock and copper starvation responses, respectively, in the unicellular green alga Chlamydomonas r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 72 publications
4
81
0
Order By: Relevance
“…It has been shown recently that the effect of CRR1 on transcription of CYC6, CPX1, and CRD1 is mediated by an opening of the chromatin structure of the respective promoter regions (Strenkert et al, 2011). Due to the constitutively open chromatin state of the CRD1 promoter under noninducing conditions, the authors suggested that an additional unknown factor is probably involved in CRD1 gene expression (Strenkert et al, 2011).…”
Section: Activation Of Hyda1 Expression Requires Additional Regulatormentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown recently that the effect of CRR1 on transcription of CYC6, CPX1, and CRD1 is mediated by an opening of the chromatin structure of the respective promoter regions (Strenkert et al, 2011). Due to the constitutively open chromatin state of the CRD1 promoter under noninducing conditions, the authors suggested that an additional unknown factor is probably involved in CRD1 gene expression (Strenkert et al, 2011).…”
Section: Activation Of Hyda1 Expression Requires Additional Regulatormentioning
confidence: 99%
“…Due to the constitutively open chromatin state of the CRD1 promoter under noninducing conditions, the authors suggested that an additional unknown factor is probably involved in CRD1 gene expression (Strenkert et al, 2011).…”
Section: Activation Of Hyda1 Expression Requires Additional Regulatormentioning
confidence: 99%
“…In plants and yeast, the histone variant H2A.Z is possibly a determinant in gene regulation associated with temperature responsiveness (Kumar and Wigge, 2010). In the green alga Chlamydomonas reinhardtii, HS-activated HSF1 is also involved in chromatin remodeling (Strenkert et al, 2011). Mechanisms of gene regulation affected by HS are more complicated by including the translational control.…”
mentioning
confidence: 99%
“…qRT-PCR was performed using the StepOnePlus RT-PCR system (Applied Biosystems) and the Maxima SYBR Green kit from Fermentas as described previously (Strenkert et al, 2011). Primers for LHCSR3.1 were the same as described by Peers et al (2009).…”
Section: Rna Extraction and Qrt-pcrmentioning
confidence: 99%